LncRNA HIF1A-AS1 promotes the proliferation of gastric cancer cell lines through interfering with HIF1A - YIN Lijun, BO Yang, Anggelema, SONG Linlin (Jichu yixue yu linchuang)
Objective To investigate the effects of HIF1A-AS1 on the proliferation and apoptosis of gastric cancer cells lines BGC-823 and MKN28 and its possible mechanism. Methods The expression of HIF1A-AS1 in gastric cancer tissues was analyzed by bioinformatics. HIF1A-AS1 over expression and silenced BGC-823 and MKN28 cell strains were constructed. HIF1A-AS1 expression was detected by real-time PCR, cell proliferation was detected by CCK-8 assay, and apoptosis was detected by flow cytometry. Western blot was used to detect the expression of HIF1A protein in cytoplasm and nucleus and cellular immunofluorescence was used to detect HIF1A protein into nucleus. Results Models of BGC-823 and MKN28 gastric cancer cells with HIF1A-AS1 over-expression and silence were successfully constructed.HIF1A-AS1 over-expression decreased cell proliferation (P＜0.05), while HIF1A-AS1 over-expression significantly increased cell proliferation (P＜0.05). HIF1A-AS1 silencing significantly increased the apoptosis (P＜0.05), and HIF1A-AS1-over expression significantly decreased the apoptosis (P＜0.05). HIF1A-AS1 silencing inhibited the nucleation of HIF1A protein and over-expression promoted the nucleation of HIF1A protein. HIF1A-AS1 silencing significantly decreased the expression of HIF1A cytoplasmic protein (P＜0.05) and over-expression of HIF1A-AS1 significantly increased the expression of HIF1A cytoplasm protein (P＜0.05). HIF1A-AS1 silencing significantly decreased the expression of HIF1A nuclear protein (P＜0.05) while HIF1A-AS1 over-expression significantly increased the expression of HIF1A nuclear protein (P＜0.05). Conclusions HIF1A-AS1 may promote the proliferation and inhibit apoptosis of BGC-823 and MKN28 gastric cancer cells by regulating the expression of parental gene HIF1A.